2001
DOI: 10.1890/0012-9658(2001)082[3295:facogi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation and Competition on Gradients in Alpine Plant Communities

Abstract: We conducted a neighbor removal experiment in natural alpine plant communities of the southwestern Alps to test for the relative importance of competitive and facilitative interactions along elevational and topographical gradients. The experimental sites were chosen to encompass most of the floristic diversity observed along gradients of elevation and topography, which are the two main ecological gradients associated with alpine plant communities in the western Alps. The effects of neighbor removal on the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

66
543
8
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 642 publications
(636 citation statements)
references
References 87 publications
66
543
8
4
Order By: Relevance
“…These results suggest that, under the effects of accelerated warming, the absence of an important nurse species in a new alpine area targeted for upward migration will have a negative effect on plant diversity by impeding the establishment of associated plants (e.g., Myrosmodes sp., Lupinus microphyllus ; Figure 3). This upholds the hypothesis that the future of (alpine) biodiversity could be partly dependent on facilitative and mutualistic interactions among organisms, required to avoid “chains of extinction” (Choler et al, 2001; Brooker et al, 2008; Bellard et al, 2012). …”
Section: Facilitation and The Upward Migration Of Alpine Speciessupporting
confidence: 77%
See 1 more Smart Citation
“…These results suggest that, under the effects of accelerated warming, the absence of an important nurse species in a new alpine area targeted for upward migration will have a negative effect on plant diversity by impeding the establishment of associated plants (e.g., Myrosmodes sp., Lupinus microphyllus ; Figure 3). This upholds the hypothesis that the future of (alpine) biodiversity could be partly dependent on facilitative and mutualistic interactions among organisms, required to avoid “chains of extinction” (Choler et al, 2001; Brooker et al, 2008; Bellard et al, 2012). …”
Section: Facilitation and The Upward Migration Of Alpine Speciessupporting
confidence: 77%
“…Alpine plant communities have been widely used by ecologists over the last two decades to infer patterns and mechanisms of plant–plant interactions, in particular because mountain environments provide abrupt stress variations along elevation gradients (Körner, 2007). Studies conducted in these environments have provided major contributions to the definition and further refinements of the SGH (Choler et al, 2001; Callaway et al, 2002; Maestre et al, 2009; He et al, 2013). In most alpine environments, greater facilitation is observed at higher elevation, i.e., in more stressful conditions—readers are referred to the specific cases in dry alpine environments reported by Cavieres et al (2006) and Michalet et al (2014) where two opposing stress gradients were found.…”
Section: Introductionmentioning
confidence: 99%
“…An additional criticism of the community phylogenetic approach is that phylogenetic clustering may also be generated by interspecific competition when community structure is mainly shaped by competitive hierarchy fitness differences (Mayfield & Levine, 2010). In high-alpine environments, however, it is widely expected that competitive interactions will be reduced and that plant-plant interactions will be dominantly positive through ecological facilitation (Choler et al ., 2001). Therefore, alpine areas are well suited for studying the mechanisms of biodiversity origins and species coexistence using a comparative community phylogenetic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when species abundance peaks at intermediate resources to form a unimodal curve [2,3], this pattern may represent a self-limiting optimum [4][5][6] or a contraction owing to negative biotic interactions that overwhelm the species where resources are high [1,7,8]. Conversely, positive biotic interactions can extend the fundamental niche beyond that of the realized niche by enhancing access to limiting resources [9][10][11]. This requires, however, that resource conditions are optimal for both mutualists, and failed or limited facilitation can result in contracted response patterns similar to those created by competitive interactions [12,13].…”
Section: Introductionmentioning
confidence: 99%